2022
DOI: 10.1097/inf.0000000000003763
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for Treatment of Children and Young Adults With Severe Acute COVID-19: Experience at a Quaternary-care Children’s Hospital

Abstract: We describe the clinical characteristics and outcomes of 16 children and young adults with severe acute COVID-19 who were treated with tocilizumab. Patients who were discharged by day 28 were more likely to be treated with tocilizumab earlier in their COVID-19 illness and had lower ferritin and interleukin-6 levels compared with those who were not discharged by day 28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although one child died of bacterial infection, IL-6 and other indicators decreased rapidly after early blood puri cation treatment, indicating that blood puri cation has a certain positive effect in managing cytokine storms [14]. Teoh et al analyzed the clinical features and outcomes of 16 children and young adults with severe acute COVID-19 treated with tocilizumab and found that delayed administration after admission to PICU may be an important predictor of poor prognosis [15]. One of our patients died of a severe bacterial infection (Escherichia coli) after blood puri cation and tocilizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although one child died of bacterial infection, IL-6 and other indicators decreased rapidly after early blood puri cation treatment, indicating that blood puri cation has a certain positive effect in managing cytokine storms [14]. Teoh et al analyzed the clinical features and outcomes of 16 children and young adults with severe acute COVID-19 treated with tocilizumab and found that delayed administration after admission to PICU may be an important predictor of poor prognosis [15]. One of our patients died of a severe bacterial infection (Escherichia coli) after blood puri cation and tocilizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab (Actemra®) was granted an Emergency Use Authorization (EUA) by the FDA for the treatment of hospitalized pediatric patients (aged 2 years and above) receiving systemic corticosteroids, requiring supplemental oxygen, non-invasive or invasive mechanical ventilation, or extracorporeal membrane oxygenation (ECMO). A retrospective study suggests that early administration of tocilizumab, as opposed to delayed administration after admission to the PICU, may result in better outcomes [163] . A clinical trial has been initiated to assess the pharmacokinetics, pharmacodynamics, and safety of tocilizumab in pediatric patients hospitalized with COVID-19 [164] .…”
Section: Management and Essential Medicationsmentioning
confidence: 99%
“…There has been an emergency use authorization (EUA) for children over 2 years of age who also are on supplemental oxygen and systemic steroids. The dose is 12 mg/kg in children weighing <30 kg, 8 mg/kg (max: 800 mg) in children > 30kg to be repeated once after 8 hours is there is no response [77,78]. However, the risk and benefits of the treatment are not clear yet and require further evaluation [78] Outpatient management with antiviral medications have been recommended in patients who are at high risk for progression to severe disease like; patients with one or more underlying medical conditions, patient who are immunocompromised, patients who are dependent on medical technology, un immunized, and obese patients [79].…”
mentioning
confidence: 99%
“…The dose is 12 mg/kg in children weighing <30 kg, 8 mg/kg (max: 800 mg) in children > 30kg to be repeated once after 8 hours is there is no response [77,78]. However, the risk and benefits of the treatment are not clear yet and require further evaluation [78] Outpatient management with antiviral medications have been recommended in patients who are at high risk for progression to severe disease like; patients with one or more underlying medical conditions, patient who are immunocompromised, patients who are dependent on medical technology, un immunized, and obese patients [79]. The medications that have been recommended for use are nirmatrelvir-ritonavir which is a protease inhibitor and prevents viral replication and approved for children over 12 years of age [80] and molnupiravir which is a nucleoside analogue that also prevents viral replication and has been approved for patients older than 18 years of age [81] both are given for five days.…”
mentioning
confidence: 99%